2018
DOI: 10.1021/acsenergylett.8b01178
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Activity and Dissolution on RuO2 under Oxygen Evolution Conditions: Particles versus Well-Defined Extended Surfaces

Abstract: Rutile RuO2 catalysts are the most active pure metal oxides for oxygen evolution; however, they are also unstable towards dissolution. Herein, we study the catalytic activity and stability of oriented thin films of RuO2 with the (111), (101) and (001) orientations, in comparison to a (110) single crystal and commercial nanoparticles. These surfaces were all tested in aqueous solutions 0.05 M H2SO4. The initial catalyst activity ranked as follows: (001) > (101) > (111) ≈ (110). We complemented our activity data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
180
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(204 citation statements)
references
References 49 publications
13
180
0
2
Order By: Relevance
“…While previous studies [3][4][5] suggest that active dissolution of the material results in the best activities, our results suggest that an activity enhancement can be achieved by an initial dissolution (preconditioning) that creates the variety of reaction sites but that the dissolution does not have to continue for high OER activities. This agrees with recent experimental findings for RuO2 thin films, which show that while the surface orientation with the initially highest dissolution rate results in the best activities, an ongoing dissolution is not necessary for highly active surfaces 6 . It was also reported that the binding energy of reaction intermediates is not a good descriptor for the activity of metastable materials 5 .…”
Section: Resultssupporting
confidence: 93%
“…While previous studies [3][4][5] suggest that active dissolution of the material results in the best activities, our results suggest that an activity enhancement can be achieved by an initial dissolution (preconditioning) that creates the variety of reaction sites but that the dissolution does not have to continue for high OER activities. This agrees with recent experimental findings for RuO2 thin films, which show that while the surface orientation with the initially highest dissolution rate results in the best activities, an ongoing dissolution is not necessary for highly active surfaces 6 . It was also reported that the binding energy of reaction intermediates is not a good descriptor for the activity of metastable materials 5 .…”
Section: Resultssupporting
confidence: 93%
“…[ 38,53 ] The higher OER catalytic activity of CoRu–MoS 2 than that of Co–MoS 2 is ascribed to the RuO 2 nanoparticles, since this oxide is a well‐known active OER catalyst. [ 54,55 ] The Ru–MoS 2 , in contrast, did not show any activity due to the negligible oxidation of Ru into RuO 2 . Therefore, we suggest that the Co dopant induces the formation of RuO 2 by following the redox reactions of Co 3+ + e − → Co 2+ ( E ° = 1.92 V) and Ru(s) + 2H 2 O(l) → RuO 2 (s) + 4H + + 4e − ( E ° = −0.68 V).…”
Section: Resultsmentioning
confidence: 98%
“…Beyond, the applied overpotential might provide further evidence for the separated apexes: RuO 2 faces severe stability problem under harsh anodic reaction conditions, which is ascribed to the increasing OER current if the applied overpotential is raised. In the overpotential regime of η CER <0.125 V in an acidic electrolyte solution (pH<1) it has been demonstrated by online electrochemical mass spectrometry (OLEMS) that the current affiliated with oxygen evolution is negligible small .…”
Section: Resultsmentioning
confidence: 99%